Size-Dependent Multiple-Scattering Effects of Mesoporous TiO2 Beads Distinguished by Optical Coherence Tomography - Ling-Hsuan Tsai; Po Nien Yang; Yen-Chen Shih; King-Fu Lin; Chung-Chih Wu; Hoang Yang Lin (IEEE Photonics Journal)
In this study, we propose a new analysis method using optical coherence tomography to further use the diffusive reflectance measurement to quantify the contribution of the size-dependent multiple-scattering effects of mesoporous TiO2 beads. The diffusive reflectance results from the complex interactions between light and the scattering particles, and influences the slopes of the associated depth-dependent A-scan profiles, which can be fitted based on the extended Huygens–Fresnel model to quantify the contribution ratio of the multiple-scattering effects to the single scattering effects. The mesoporous TiO2 beads with average diameter of 300 nm show higher contribution percentage of multiple-scattering effects inducing reflectivity enhancement in the longer wavelength region. The contribution ratio of multiple-scattering effects can be distinguished numerically, and is enhanced from 5% to 40% and then decreased to 20% for the bead diameters ranging from 20 to 300 nm and then to 500 nm, respectively. The calculated scattering coefficients are 13.5 ± 0.6 mm–1, 16.5 ± 0.6 mm–1, 20.2 ± 0.6 mm–1, and 18.5 ± 0.6 mm–1, respectively.